2018
DOI: 10.1371/journal.pone.0206181
|View full text |Cite|
|
Sign up to set email alerts
|

Eocene metatherians from Anatolia illuminate the assembly of an island fauna during Deep Time

Abstract: Island biotas have disproportionately influenced the history and development of evolutionary biology, but understanding their genesis and evolution across geological timescales has been hindered by a poor fossil record. Here we augment the insular Eocene (~43 Ma) mammalian fauna known from the Pontide terrane of central Anatolia by describing two new metatherian taxa (stem marsupials) from the Lülük Member of the Uzunçarşıdere Formation in the Orhaniye Basin. Geological and paleontological data indicate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 39 publications
3
40
0
Order By: Relevance
“…This is sustained by a large number of taxa shared between Africa and South America, but also with other landmasses and especially India, including hystricognath rodents, anthropoid monkeys, afrotherian mammals, pipid frogs, freshwater fishes (cichlids and aplocheiloids), birds (parrots, hoatzins, phororhacoids), and lizards (geckos), and Malpighiaceae, Asteraceae, and Bromeliaceae among plants 52,[54][55][56][57][58][59] . Further support for this interchange includes the finding of several lineages of metatherians, anthropoid monkeys and hystricognath rodents in South America, indicating multiple dispersals between South America and Africa and vice-versa during the Paleogene [60][61][62][63][64] . As enumerated above, the evidence indicating a fluid interchange between South America and other Southern Hemisphere landmasses and India has been greatly increasing during the last years (see below).…”
Section: Litoptern Affinities and The Splendid Isolation Of South Amementioning
confidence: 94%
“…This is sustained by a large number of taxa shared between Africa and South America, but also with other landmasses and especially India, including hystricognath rodents, anthropoid monkeys, afrotherian mammals, pipid frogs, freshwater fishes (cichlids and aplocheiloids), birds (parrots, hoatzins, phororhacoids), and lizards (geckos), and Malpighiaceae, Asteraceae, and Bromeliaceae among plants 52,[54][55][56][57][58][59] . Further support for this interchange includes the finding of several lineages of metatherians, anthropoid monkeys and hystricognath rodents in South America, indicating multiple dispersals between South America and Africa and vice-versa during the Paleogene [60][61][62][63][64] . As enumerated above, the evidence indicating a fluid interchange between South America and other Southern Hemisphere landmasses and India has been greatly increasing during the last years (see below).…”
Section: Litoptern Affinities and The Splendid Isolation Of South Amementioning
confidence: 94%
“…Such a dispersal, at least from the Balkans to central Europe seems to have taken place slightly later than the above discussed northern route (i.e., around 31 Ma versus around 33 Ma; see Mennecart et al 2018b). Interestingly, it has also been recently demonstrated, again on the basis of mammal finds, that during the Eocene, the area of central Anatolia was an island environment (the "Pontide terrane") possessing a remarkable diversity of peculiar and endemic forms, all of which became ultimately extinct during the Oligocene when the loss of the insular status of the area permitted the arrival of several other mammal lineages from both Europe and Asia (see Métais et al 2018). Nevertheless, given the absence of adequate Oligocene amphibian and reptile remains from the area of Anatolia and the southern Balkans, such southern dispersal route for the herpetofauna as well and any relevant biogeographic patterns have remained obscure.…”
Section: A B Cmentioning
confidence: 99%
“…A Paleocene dispersal of metatherians from South America to Africa could not only account for the inferred affinities of Kasserinotherium but also for the presence of anatoliadelphyid polydolopimorphians (Anatoliadelphys, Orhaniyeia) in the middle Eocene of Central Anatolia (Turkey). Interestingly, Métais et al (2018) found phylogenetic affinities between anatoliadelphyids and South American and Australian bunodont polydolopimorphian metatherians such as Palangania, Chulpasia and Thylacotinga. "We hypothesize that basal polydolopimorphians were actually present in Africa during the early and/ or middle Eocene, whence they rafted northward across Neotethys to colonize the Pontide terrane."…”
Section: Dual Origin Of African Metatherians?mentioning
confidence: 99%